Dinamika Penerapan Pembelajaran Multiliterasi dengan Perspektif Ekologi: Kajian Narrative Inquiry - Sugiarti Sugiarti; Arti Prihatini; Eggy Fajar Andalas (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Teachers are required to have competence in implementing ecological multiliteracy learning in the classroom. However, teachers of SMA Aisyiyah Boarding School Malang (SMA ABSM) have tried to implement it, but still have difficulties implementing multiliteracy learning with an ecological perspective. Therefore, this study aims to describe the dynamics of the application of multiliteracy-based learning with an ecological perspective. This research method is a narrative inquiry with the subject of five ABSM High School teachers. The results showed that, in general, teachers have sufficient knowledge about multiliteracy-based learning. However, a small percentage of teachers still do not understand it enough. In implementing multiliteracy-based learning, teachers still experience obstacles in providing multiliteracy-based materials, time management, and learning innovation constraints. In addition, obstacles arise due to students' lack of interest in reading and literacy skills. However, teachers try to apply multiliteracy-based learning to the subjects they teach with an ecological perspective. The application of multiliteracy learning is integrated through several considerations: the variety of learning resources with an ecological perspective, subjects taught, the stages of implementing multiliteracy-based learning, and learning model innovation. Learning resources are presented multimodally using text, sound, images, and audiovisuals. All subjects have their own characteristics in integrating multiliteracy-based learning with an ecological perspective in science, social, and language subjects. Learning innovation is carried out by teachers by integrating multiliteracy activities in the syntax of the learning model.